2010
DOI: 10.1002/cbdv.200900314
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Biodiversity for Cellulosic Biofuel Production

Abstract: Industrial production of solvents such as EtOH and BuOH from cellulosic biomass has the potential to provide a sustainable energy source that is relatively cheap, abundant, and environmentally sound, but currently production costs are driven up by expensive enzymes, which are necessary to degrade cellulose into fermentable sugars. These costs could be significantly reduced if a microorganism could be engineered to efficiently and quickly convert cellulosic biomass directly to product in a one-step process. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…GH3 enzymes from C. fimi release monosaccharides from plant cell wall polysaccharides. ␤-1,4-Linked xylosides and glucosides are common moieties found in plant cell walls and are of particular importance for biomass conversion for biofuel production (24). The activity with pNP-linked sugars suggested that the four GH3 enzymes may have activity against ␤-1,4-linked xylosides or glucosides.…”
Section: Resultsmentioning
confidence: 99%
“…GH3 enzymes from C. fimi release monosaccharides from plant cell wall polysaccharides. ␤-1,4-Linked xylosides and glucosides are common moieties found in plant cell walls and are of particular importance for biomass conversion for biofuel production (24). The activity with pNP-linked sugars suggested that the four GH3 enzymes may have activity against ␤-1,4-linked xylosides or glucosides.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, C. cellulolyticum has a sequenced genome (GenBank accession NC_011898.1) and there exist well-established DNA transfer techniques (24) and gene overexpression methods (10) for it. As a potential CBP organism in its own right, C. cellulolyticum can not only utilize cellulose similar to C. thermocellum but also utilize additional sugars freed from hemicellulose degradation, including xylose, arabinose, fructose, galactose, mannose, and ribose (9).…”
mentioning
confidence: 99%
“…cellulolyticum, as a potential CBP organism, similar to C. thermocellum can utilize cellulose as well as other sugars released from hemicellulose degradation, including xylose, fructose, galactose, arabinose, mannose, and ribose (Gowen and Fong, 2010;Higashide et al, 2011). Recently, investigations have been focused on engineering of these bacteria to enhance their CBP butanol production.…”
Section: Genetic Engineering For Cbp Butanol Production In Clostridiamentioning
confidence: 99%